MATRIKS RELASI PREFERENSI FUZZY TERITLAK DAN APLIKASINYA UNTUK PEMBUATAN KEPUTUSAN - Siti, Khabibah; ., Farikhin; Puspita, Nikken Prima (MATEMATIKA, 2016)
In the paper, we explore Dempster-Shaver’s theory and fuzzy preference relations for a decision making. Firstly, we discuss some necessary anf suficient conditions for constructing additive consistency fuzzy preference relation. With respect to the Deng et. al.’s work, we combined these to construct a method for decision making. Finally, two examples are presented as illustrations of the effectiveness of the proposed method.